2011
DOI: 10.1002/ijc.26060
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of microRNA‐204 mediates migration and invasion of endometrial cancer by regulating FOXC1

Abstract: TXMicroRNAs (miRNAs) regulate mRNA stability and protein expression, and certain miRNAs have been demonstrated to act either as oncogenes or tumor suppressors. Differential miRNA expression signatures have been documented in many human cancers but the role of miRNAs in endometrioid endometrial cancer (EEC) remains poorly understood. This study identifies significantly dysregulated miRNAs of EEC cells, and characterizes their impact on the malignant phenotype. We studied the expression of 365 human miRNAs using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
128
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(146 citation statements)
references
References 32 publications
12
128
0
Order By: Relevance
“…These results correspond with observations presented in other EEC studies and implicate oncogenic roles of miR-183, miR-96, miR-182 and miR-9 in EEC. 17,19,36 Decreased expression of miR-410, which was revealed in our set of EEC samples, was previously reported in only one study. 30 Interestingly, Ratner et al observed downregulation of miR-487b, which occupies the same locus on chromosome 14 (14q32.31).…”
Section: Early Detection and Diagnosissupporting
confidence: 79%
See 1 more Smart Citation
“…These results correspond with observations presented in other EEC studies and implicate oncogenic roles of miR-183, miR-96, miR-182 and miR-9 in EEC. 17,19,36 Decreased expression of miR-410, which was revealed in our set of EEC samples, was previously reported in only one study. 30 Interestingly, Ratner et al observed downregulation of miR-487b, which occupies the same locus on chromosome 14 (14q32.31).…”
Section: Early Detection and Diagnosissupporting
confidence: 79%
“…16 Although a number of studies suggested miRNAs involvement in EEC pathogenesis, only few of them involved large groups of patients and addressed issues concerning the influence of clinicopathological features on miRNAs expression. [17][18][19][20] Similarly, diagnostic or prognostic accuracy of miRNA signatures in tissue and plasma of EEC patients has not been systematically studied. Thus, the aim of our study was to define tissue and plasma miRNA signatures, which could potentially serve as diagnostic and prognostic markers in EEC and to investigate miRNA profiles in regard to EEC clinicopathological characteristics.…”
mentioning
confidence: 99%
“…In addition, downregulation of miR-204 has been documented in several types of cancers. [37][38][39][40][41] Decreased expression of miR-204 results in overexpression of its target, myeloid cell leukemia sequence 1 (Mcl-1) mRNA, and induces anti-apoptotic signaling in pancreatic cancers. 42 miR-204 also regulates expression of an oncogene, neurotrophic receptor tyrosine kinase B, and promotes metastasis in endometrial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…miR-7 is also upregulated in endometrial cancer, and invasion and cancer cell migration are inhibited by downregulation of miR-7 using an anti-miRNA antibody (Chung et al, 2012). In endometrioid adenocarcinoma, upregulation of miR-27 expression is surgical stage-dependent.…”
Section: Endometrial Cancer and Mirnamentioning
confidence: 99%